2019
DOI: 10.3390/ijms20051223
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Melatonin, and the Pro- and Anti-Inflammatory Networks

Abstract: Aging and various age-related diseases are associated with reductions in melatonin secretion, proinflammatory changes in the immune system, a deteriorating circadian system, and reductions in sirtuin-1 (SIRT1) activity. In non-tumor cells, several effects of melatonin are abolished by inhibiting SIRT1, indicating mediation by SIRT1. Melatonin is, in addition to its circadian and antioxidant roles, an immune stimulatory agent. However, it can act as either a pro- or anti-inflammatory regulator in a context-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
212
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(217 citation statements)
references
References 389 publications
(394 reference statements)
1
212
0
4
Order By: Relevance
“…The NF-kB signaling pathway is widely considered to be associated with the transcription of pro-inflammatory cytokines and the polarization of pro-inflammatory macrophages [40]. Yu et al showed that MSR1 was required for the lipopolysaccharide-induced activation of the NF-κB signaling pathway in macrophages [33].…”
Section: Discussionmentioning
confidence: 99%
“…The NF-kB signaling pathway is widely considered to be associated with the transcription of pro-inflammatory cytokines and the polarization of pro-inflammatory macrophages [40]. Yu et al showed that MSR1 was required for the lipopolysaccharide-induced activation of the NF-κB signaling pathway in macrophages [33].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is commonly associated with an elevated production of cytokines and chemokines, while melatonin causes a reduction in the pro-inflammatory cytokines. TNF-α, IL-1β, IL-6, and IL-8, and an elevation in the level of anti-inflammatory cytokine IL-10 [33,34].…”
Section: Melatonin and Anti-inflammationmentioning
confidence: 99%
“…Remarkably, during the last decade, the indole has been detected in several edible plants, eggs, and fish, assuming an interesting and promising role as a nutraceutical [81,82]. The compelling evidence of decreased endogenous melatonin in senescence triggered intense research on its potential role as a dietary supplement to prevent and treat aging and age-related diseases [83,84].…”
Section: Melatonin Alleviates Skeletal Muscle Disorders In Vitro Andmentioning
confidence: 99%